Evaluation of cyanex272 in the emulsion liquid membrane system for separation of thorium - Darya Ehyaie; Parisa Zaheri; Mohammad Samadfam; Fazel Zahakifar (Scientific Reports)
Abstract This study describes the use of the emulsion liquid membrane (ELM) technique to recover thorium (Th(IV)) from an aqueous nitrate solution. The components of the ELM were kerosene as a diluent, sorbitan monooleate (span 80) as a surfactant, bis(2,4,4-trimethylpentyl)phosphinic acid (Cyanex 272) as an extractant, and H2SO4 solution as a stripping reagent. Th(IV) was more successfully extracted and separated under the following favorable conditions: Cyanex272 concentration of 0.11 mol/L; 0.65 mol/L H2SO4 as a stripping phase (internal phase); feed phase (external phase) pH of 1; internal-to-membrane phase volume ratio of 1; emulsion-to-external phase volume ratio of 0.4; contact time of 25 min; and agitation speed of 300 rpm. Under these conditions, the membrane transferred Th(IV) selectively from the real leach liquor without appreciable emulsion breakage or swelling.